Biosynthesis of biotin from dethiobiotin by the biotin auxotroph Lactobacillus plantarum. - Bowman, W C (1993)
Lactobacillus plantarum requires biotin for growth. We show that in the presence of high levels of the biotin biosynthetic precursor, dethiobiotin, L. plantarum synthesizes biotin and grows in medium with dethiobiotin but without biotin. Lactobacillus casei also grew under similar conditions.